The Effect of Bank Image and Service Quality On Customer Satisfaction Dimediation Loyalty - Sumiyati Sumiyati (Syntax Corporation, 2022)
THE EFFECT OF BANK IMAGE AND SERVICE QUALITY ON CUSTOMER SATISFACTION DIMEDIATION LOYALTY In the current merger process at Bank Syariah Indonesia, there is often a buildup of customers due to the migration process, many complain about various things related to migration services as the main step in the merger process. The purpose of this study was to analyze the effect of bank image and service quality on customer satisfaction mediated loyalty. The method in this research is descriptive quantitative. The population in this study were customers of BSI Semarang Karangayu Branch with a total sample of 110 respondents. The results of this study indicate that the image of the bank has no effect on satisfaction. This is based on the t test obtained because the value of t count < t table (0.469 < 1.976). Service quality has an effect on satisfaction because the value of t count > t table (3.594 > 1.976). The image of the bank has no effect on loyalty, this is based on the t test because the value of t count < t table (0.116 < 1.976). Service quality has an effect on loyalty, this is based on the t test because the value of t count > t table (4.717 > 1.976). Satisfaction has an effect on loyalty, this is based on the t test because the value of t count > t table (10,683 > 1,976). Bank image has no effect on loyalty through satisfaction, this is because the partial effect is not significant so that it does not meet the requirements for a mediation test. Service quality has an effect on loyalty through satisfaction, this is based on the Sobel test which obtained a significance value of 0.000 less than 0.05 and a Z value of 5.8341. This shows that the effect of mediation is greater than its direct effect.